The Charter School Experience Voices from the Field - Bitz, Michael (SensePublishers : Imprint: SensePublishers, 2016)
The Charter School Experience: Voices from the Field is a unique book that presents readers with balanced perspectives from teachers, students, parents, and school leaders at charter schools across the United States. Through first-person narratives, the book highlights the delicate intricacies of what makes a school charter succeed or fail. Unlike a book written by academics far removed from the practice of education, this book gives voice to the people most impacted by charters: the families and educators who have embraced these schools for better or worse, and who now have enriching stories to tell. These experiences-embodied in introspective and moving chapters-go well beyond the news headlines and politicized studies that have spotlighted charters in the past. In this book, teachers highlight their successes and failures in charter school classrooms, parents explore decisions to enroll in charters, school leaders discuss the social missions of charters, and students write about how charter schools have impacted their lives. The result is an engaging collection of ideas for a wide audience, including people researching, attending, and making policy on charter schools in the United States and around the world. .